BANDAR SUKABUMI IN THE BEGINNING OF THE 19TH CENTURY: THE ROLE OF POLITICAL AUTHORITY IN THE DEVELOPMENT OF RIVER-CITY IN KOTAWARINGIN REGION, SOUTHWESTERN KALIMANTAN - Moh Ali Fadillah (Balai Arkeologi Kalimantan Selatan, 2020)
Kotawaringin is the name of a small kingdom founded in the first half of the 17th century, centered in Kotawaringin Lama on the upper reaches of Sungai Lamandau, in southwestern Kalimantan. In the early 19th century the royal capital was moved to Pangkalan Bun. The shift of the capital city is an important factor in the history of human geography as a cause of changes in demography and urbanization. This research aimed to find clarity about the agglomeration of river cities in terms of symbolic and pragmatic aspects. Such aspects include the origin, existence, reasons for shifting capital and the type of culture that underlies the function of Kotawaringin as a center of government and trade that grew during the early colonial period. The research used methods which were carried out by observing sites indicated as capitals and ports, combining it with studies of historical sources, as well as collecting physical evidence, including a number of symbolic objects associated with royal legitimacy. Results of contextual analysis provide a set of knowledge about the growth of river city as the implementation of the spatial planning policy of the government and the support of urban communities rooted in Malay culture. The Kingdom of Kotawaringin reached a peak of progress during the reign of Prince Ratu Imanuddin, after the capital was moved to Pangkalan Bun from Kotawaringin Lama. The location of the new capital is on the lower reaches of the Sungai Lamandau, precisely on the banks of the Sungai Arut, which was formerly called Bandar Sukabumi. Kotawaringin adalah nama sebuah kerajaan kecil yang didirikan pada paruh pertama abad ke-17 Masehi, berpusat di Kotawaringin Lama di kawasan hulu Sungai Lamandau, di barat daya Kalimantan. Pada awal abad ke-19 Masehi, ibukota kerajaan dipindahkan ke Pangkalan Bun. Pergeseran ibukota merupakan faktor penting dalam sejarah geografi manusia sebagai penyebab perubahan demografi dan urbanisasi. Penelitian ini bertujuan untuk mengetahui kejelasan tentang aglomerasi kota sungai ditinjau dari aspek simbolik dan pragmatis. Aspek-aspek tersebut mencakup asal usul, keberadaan, alasan perpindahan ibukota dan jenis budaya yang mendasari fungsi Kotawaringin sebagai pusat pemerintahan dan perdagangan yang tumbuh pada masa kolonial awal. Penelitian ini menggunakan metode yang dilakukan dengan mengamati situs-situs yang diindikasikan sebagai ibukota dan pelabuhan, memadukannya dengan studi sumber-sumber sejarah, serta mengumpulkan bukti-bukti fisik, termasuk sejumlah benda simbolis yang terkait dengan legitimasi kerajaan. Hasil analisis kontekstual memberikan seperangkat pengetahuan tentang pertumbuhan kota sungai sebagai implementasi kebijakan perencanaan tata ruang pemerintah, dan dukungan masyarakat kota yang berakar pada budaya Melayu. Kerajaan Kotawaringin mencapai puncak kemajuan pada masa pemerintahan Pangeran Ratu Imanuddin, setelah ibu kota dipindahkan ke Pangkalan Bun dari Kotawaringin Lama. Lokasi ibu kota baru berada di bagian hilir Sungai Lamandau, tepatnya di tepi Sungai Arut yang dahulu dinamai Bandar Sukabumi.